Is monthly retreatment with intravitreal bevacizumab (Avastin®) necessary in neovascular age-related macular degeneration? - Ghazi, Nicola G. (2010)
Purpose To report our short-term experience with bevacizumab in neovascular age-related macular degeneration (AMD) and recommend a new treatment strategy. Methods Retrospective chart review of 29 consecutive patients receiving 1.25 mg of intravitreal bevacizumab for AMD and completing 12 weeks of follow up. Outcome measures were best corrected visual acuity (BCVA) and optical coherence tomography (OCT) central macular thickness. Injections were repeated if no further improvement was observed. Results Twenty-nine eyes of 29 patients were included. The average BCVA improved from 20/148 at baseline to 20/106 at twelve weeks (P = 0.041). Of the 29 eyes, 25 (86.2%) had stable or improved BCVA. Average mean central macular thickness measured by OCT improved from 351 μm at baseline to 278 μm at 12 weeks (P = 0.003). Stabilization of vision and improved OCT central macular thickness were maintained for at least eight weeks following only a single injection in the majority of eyes. During the three months of follow up, only five eyes (17.2%) required repeat injections, with only three (10.3%) requiring retreatment at eight weeks and none at four weeks. No significant ocular or systemic side effects were observed. Conclusion This short-term data suggests that bevacizumab appears to be a safe and effective treatment for neovascular AMD. Injections as frequent as every month do not appear to be necessary since initial treatment effect appears to be maintained for at least eight weeks in almost all of our patients.